Science Teachers perceptions on the use of computer-based materials. - M. Shah, Parilah; Embi, Mohamed Amin; Yusof, Aminuddin; Tamuri, Ab. Halim; Din, Rosseni (Common Ground Publishing, 2008)
Malaysia embarked on the use of English as a medium of instruction for the teaching of Science (and also Mathematics) in January 2003. One of the aims was to upgrade the English language proficiency of Malaysian students. Several problems and challenges have been encountered by implementers and educators since then. One of the problems is the use of the existing computer-based science materials. Apart from the obvious and great need for more science materials, new materials need to be designed to fulfill the needs of the science students who are not competent in the English language and also the needs of the science teachers who are also lacking in the knowledge of the English language. This study examined the perceptions of the science teachers in Malaysia concerning the use of computer-based materials provided by the Ministry of Education. The findings were presented in terms of the clarity and suitability of the content, English language used, presentation of content materials, and adequacy of materials and facilities. Based on the results, several suggestions are put forward so that a more systematic approach could be employed in designing better computer-based materials for the teachers and students.